Деякі питання регламентації початку досудового розслідування у кримінальному процесі України - Глобенко, Г. І.; Globenko, G. I.; ORCID: http://orcid.org/0000-0002-1533-9213 (Вісник Харківського національного університету внутрішніх справ. - 2016. - № 3(74). - С. 76–84, 2016)
Здійснено аналіз положень кримінального процесуального законодавства України та деяких інших країн пострадянського простору, що стосуються початку досудового розслідування. Розглянуто думки науковців з питань, що досліджуються, та надано їх оцінку. Сформульовано та обґрунтовано пропозиції щодо вдосконалення процесуальних норм, які стосуються предмета дослідження.

It is indicated that the current Criminal Procedural Code of Ukraine contains a number of novels, one of which is the rejection of the institution of initiating criminal proceedings. However, analysis of the content of procedural norms of most postSoviet countries that regulate the initiation of the pre-trial investigation indicates that most of them have a stage of initiation of a criminal case. Besides, they regulated in detail the procedure of pre-investigation check. It is noted that success of the investigation and court hearing of criminal offenses under the law of Ukraine on criminal liability depends on the stage of initiating criminal proceedings. Initiation of criminal proceedings in the domestic criminal procedure is a fundamentally new and starts from the moment of data entry on a criminal offense to the Unified Register of pre-trial investigations. A similar procedure is assumed to be in the legislation of Georgia and Kazakhstan. Opposite points of view of scholars are contained in the legal literature, who express their concerns regarding the current procedure of initiating pre-trial investigation. This is primaraly due to the fact that the Criminal Procedural Code of Ukraine does not provide the procedure for making procedural decision on its initiation. Besides a number of issues regarding: the form and content of the statement or report on committed criminal offense; taking all possible measures to prevent criminal offense or its termination; implementing security measures of the participants in criminal proceedings; features of procedural activities of some officials relating to the initiation of pre-trial investigation is not regulated.

Осуществлён анализ положений уголовного процессуального законодательства Украины и других стран постсоветского пространства, касающихся начала досудебного расследования. Рассмотрены точки зрения учёных по исследуемым вопросам и дана их оценка. Сформулированы и обоснованы предложения по совершенствованию процессуальных норм, относящихся к предмету исследования.
Some issues of regulating the initiation of pre-trial investigation in the criminal procedure of Ukraine
Некоторые вопросы регламентации начала досудебного расследования в уголовном процессе Украины
Глобенко, Г. І. Деякі питання регламентації початку досудового розслідування у кримінальному процесі України / Г. І. Глобенко // Вісник Харківського національного університету внутрішніх справ. - 2016. - № 3(74). - С. 76–84.
Глобенко Г. І. "Деякі питання регламентації початку досудового розслідування у кримінальному процесі України." Вісник Харківського національного університету внутрішніх справ 3 (2016): 76-84.
Globenko, G.I. (2016), “Some issues of regulating the initiation of pre-trial investigation in the criminal procedure of Ukraine” [Deiaki pytannia rehlamentatsii pochatku dosudovoho rozsliduvannia u kryminalnomu protsesi Ukrainy], Visnyk Kharkivskoho Natsionalnoho Universytetu Vnutrishnikh Sprav, No. 3, pp. 76–84.
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; поцесуальні рішення; початок досудового розслідування; слідчий; прокурор; кримінальне правопорушення; Єдиний реєстр досудових розслідувань; Unified Register of pre-trial investigations; procedural decision; initiation of pre-trial investigation; investigator; prosecutor; criminal offense; процессуальные решения; начало досудебного расследования; следователь; прокурор; уголовное правонарушение; Единый реестр досудебных расследований